An Adaline based arcing fault detection algorithm for single-pole autoreclosers - Karacasu, Ozgur; Hocaoglu, M. Hakan (Elsevier Science Sa, 2011)
In this paper, a new Adaline based adaptive single-pole autorecloser algorithm is proposed to discriminate permanent and transient faults in HV transmission lines. The proposed algorithm is implemented by processing only terminal voltages and also used to estimate secondary arc extinction time. The algorithm is simulationally analyzed using ATP version of EMTP by varying fault locations and pre fault loading conditions to demonstrate the capabilities and limitations of the method. In addition to that, measured data, which are taken from an actual power system, are also used for testing the algorithm. Results show that the method can successfully be implemented for real time application and computationally less expensive when compared with other methods. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Adaline; Adaptive single pole autorecloser; Arcing faults; Secondary arc